Pendekatan Dinamika Sistem dalam Manajemen Rantai Pasokan pada Kebijakan Manajemen Gas Alam: Studi Kasus Indonesia: Pendekatan Dinamika Sistem dalam Manajemen Rantai Pasokan pada Kebijakan Manajemen Gas Alam: Studi Kasus Indonesia - Dliyaa Ul Haq; Hari Purnomo (Journal Science Innovation and Technology (SINTECH), 2026)
This study employs a system dynamics approach using Causal Loop Diagrams (CLDs) to explore the complex interactions between infrastructure development, regulatory policies, and market behavior in Indonesia's Natural Gas Management supply chain system. The CLDs identify twelve key feedback loops across six interconnected subsystems: Distribution & Logistics, Demand & Consumption, Cost & Investment, Regulation & Policy, Technology & Innovation, and Industry & Market Adoption. These loops reflect the reinforcing and balancing dynamics that influence supply chain performance indicators such as cost efficiency, responsiveness, scalability, and sustainability. Key findings indicate that infrastructure limitations, regulatory delays, and investment uncertainty are key constraints to optimal distribution. Based on the CLD analysis, five policy recommendations are proposed to improve supply chain performance: aligning infrastructure investment with regional demand, performance-based subsidy allocation, digital innovation in logistics, adoption-based policy design, and regulatory simplification. The study provides a structured framework for energy policymakers and stakeholders to improve the effectiveness and resilience of Indonesia's natural gas distribution system during its clean energy transition.